Best Answer

x = 10

Minus 6 times 10 = minus 60

Add 3 to minus 60 = minus 57

Minus 6 times 10 = minus 60

Add 3 to minus 60 = minus 57

Q: What is -6x plus 3 equals -57?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

x = -3

y=(6x-5)/3

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

Related questions

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

6x plus 3 equals to 8x plus 14 would lead to x = - 5.5.

x = -3

y=(6x-5)/3

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

9x + 3 - 6x - 2 = 3x + 1

-6x+3 = -7-5x 7+3 = 6x-5x 10=x

6x + 2 = 6 6x = 4 x = 2/3

6x + 3 = 2x + 5 4x = 2 x=1/2

It is: 3x2+6x-11 = 0

x=-6,5